Hubungan tingkat pengetahuan ibu mengenai pemenuhan gizi 1000 hari pertama kehidupan dengan kejadian underweight - Fitry Ramdani; Muhammad Noris; Dea Zara Avila; Muammar Iksan (Holistik Jurnal Kesehatan, 2026)
Background: Being underweight is a key indicator reflecting the combined impact of acute and chronic malnutrition. Although various countries have implemented nutrition interventions, progress remains insufficient to ensure the achievement of all global nutrition targets by 2030. Findings from the 2025 Joint Child Malnutrition Estimates (JME) highlight the need for intensified efforts to prevent and address child malnutrition, including underweight status, by improving access to nutritious food and quality healthcare services, as well as promoting optimal child-feeding practices. Purpose: To analyze the relationship between maternal knowledge regarding the "First 1000 Days of Life" and the incidence of underweight status. Method: This quantitative study employed an observational analytic design with a cross-sectional approach and was conducted at the East Dompu Community Health Center in June 2026. Non-probability purposive sampling was used, resulting in a sample size of 77 respondents. Research instruments included a questionnaire on nutritional intake during the first 1000 days of life and anthropometric measurements to determine the children's nutritional status. Data were analyzed using the Chi-Square test with a significance level of p<0.05. Results: A total of 24 (31.2%) children under five were underweight, while 53 (68.8%) were not. The results showed that the proportion of underweight cases was higher among mothers with a low level of knowledge compared to those with adequate or good levels of knowledge. Conclusion: There is a significant relationship between maternal knowledge regarding nutritional intake during the first 1000 days of life and the incidence of underweight status in children under five (p=0.017; p<0.05). Suggestion: Future initiatives should focus on enhancing education and outreach regarding nutrition during the first 1000 days of life through integrated health posts, classes for mothers of young children, nutrition counseling, and the empowerment of health volunteers. Sustained education is expected to improve mothers' knowledge, enabling them to adopt better feeding and caregiving practices to prevent underweight conditions among young children.   Keywords: First 1000 Days of Life; Maternal Knowledge; Nutritional Status; Under-Five Children; Underweight.